2015
DOI: 10.1186/s13104-015-1820-6
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and perceptions of stroke: a cross-sectional survey in rural and urban Uganda

Abstract: BackgroundInformation regarding the increasing burden of non-communicable diseases such as stroke is largely unknown among the vulnerable communities. This analysis, which is part of a larger U.S. National Institute of Heath-funded Medical Education Partnership Initiative neurological disorder survey, assessed community knowledge and attitudes on stroke and stroke risk factors.MethodsA population cross-sectional survey was conducted in urban and rural Mukono, district, central Uganda. Through the systematic sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
51
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 26 publications
13
51
5
1
Order By: Relevance
“…More than half (51.4%) of the participants identi ed ve or more risk factors. Similar to our ndings, other community based studies have also reported low level of knowledge of risk factors for CVDs in the general population [13][14][15]37]. On the contrary, high knowledge has been reported among studies that focused on special populations like health care providers [41,42], secondary school teachers [23] and among staff of tertiary institution [43], meaning that education level has implication on health-related knowledge.…”
Section: Knowledge Of Risk Factors For Cvdssupporting
confidence: 88%
See 1 more Smart Citation
“…More than half (51.4%) of the participants identi ed ve or more risk factors. Similar to our ndings, other community based studies have also reported low level of knowledge of risk factors for CVDs in the general population [13][14][15]37]. On the contrary, high knowledge has been reported among studies that focused on special populations like health care providers [41,42], secondary school teachers [23] and among staff of tertiary institution [43], meaning that education level has implication on health-related knowledge.…”
Section: Knowledge Of Risk Factors For Cvdssupporting
confidence: 88%
“…Our ndings of higher CVD knowledge among men differs from other studies which reported higher CVD knowledge among females [40,51]. Nonetheless, several other studies have reported insigni cant gender differences in CVD knowledge [15,[52][53][54]. Higher CVD knowledge in women has been attributed to less working time among women which gives them more leisure time to watch and listen to mass media such as radio, television and newspaper [40].…”
Section: Factors Associated With Cvd Knowledgecontrasting
confidence: 85%
“…The sample size of the study was 377. No one identifies cigarette smoking as a risk factor of stroke and most of the subjects (77%) did not know about the organ affected by stroke [19]. The present study conducted to assess the awareness and attitude of hypertensive and non-hypertensive regarding stroke and its prevention among selected ward of Nayarambalam Panchayat, Ernakulam, and give them adequate teaching in future it is needed.…”
Section: Introductionmentioning
confidence: 91%
“…For example, in Ghana, traditional healers have been incorporated as providers into their National Healthcare Delivery System [38]. Traditional and faith healers are often sought after to care for diabetes [39], hypertension [40] or adverse CVD outcomes such as stroke [41].…”
Section: Face the Fact: Stroke Is Treatable Awareness Access Actionmentioning
confidence: 99%